Incorporação de nanocargas em copolímeros tribloco pelo método de mistura em base solvente - Accorsi, Tiago (2013)
Thermoplastic elastomers, like triblock copolymers, more specifically SBS with linear arrangement, were used to obtain polymeric nanocomposites. Employing spherical TiO2 nanofiller and nanofiller clay with lamellar structure, through mixing method, based on solvent followed by dispersion into mechanical stirring and ultrasound batch, which nanofiller were incorporated in quantities of 0,5%, 1%, 2% and 3% relative to the polymeric matrix mass. The characterization was done using thermal mechanical analytical methods like thermal gravimetric analysis (TGA) and dynamic mechanical thermal analysis (DMTA). The monitoring of the morphological structure of nanocomposite and nanofiller was performed by scanning electron microscopy. The results indicate the availability of the proposed technique for incorporation of nanofillers into the matrix and highlight the requirement for surface treatments for improved performance. The use of nanofillers with distinct characteristics can be used for directing the studies of the relation with charge and polymeric matrix and evaluation of properties in charge-matrix interface.